Tinjauan Yuridis Tentang Kebijakan Penanganan Narapidana Lansia (Suatu Analisis Terhadap Kesejahteraan dan Kesehatan Mental di Lembaga Pemasyarakatan Kelas II A Kupang) - LeoDima, Harmingganov; Amalo, Heryanto; Fanggi, Rosalind Angel (Law Faculty, Nusa Cendana University, 2025)
The increasing number of elderly inmates in correctional institutions presents new challenges for Indonesia’s legal system and correctional policy, particularly in the context of Eastern Indonesia. As part of the correctional population, elderly inmates have specific needs that are not yet fully accommodated by the existing system. This study aims to analyze the policy on the treatment of elderly inmates at Class IIA Correctional Facility in Kupang and assess its effectiveness in ensuring their well-being and mental health, including identifying key obstacles and formulating adaptive rehabilitation approaches. The research adopts an empirical juridical method by combining normative analysis of relevant legislation with field studies conducted through interviews, observation, and documentation. The findings reveal that current policies are insufficiently responsive to the specific conditions of elderly inmates. Key issues identified include the limited availability of medical personnel and mental health services, inadequate elderly-friendly infrastructure, and the absence of rehabilitation programs tailored to their physical and psychosocial conditions. This study concludes that the correctional system remains oriented toward a standard model that fails to comprehensively address the needs of vulnerable groups. Therefore, there is an urgent need for participatory correctional policies based on individual needs and strengthened rehabilitative approaches. Moreover, this research contributes to the enrichment of legal literature on correctional policies for elderly inmates at the regional level, particularly in Eastern Indonesia, which has received limited attention in academic discourse.